Review of the 94th Annual Meeting of the British Association of Dermatologists, Glasgow 2014. (May 2015) - Porter, R.M.; George, S.M.C.
Summary This is a review of the 94th Annual Meeting of the British Association of Dermatologists, held in Glasgow from 1 to 3 July 2014. The conference covered some of the latest developments in the treatment of atopic dermatitis, psoriasis and cancer, a follow‐up on the methylisothiazolinone contact allergy epidemic, advances in genetically inherited disorders and somatic mutations underlying birth marks. In addition, there was an international perspective on vitiligo, leprosy and HIV, and a session discussing the regulatory process behind pharmaceutical development.